UNVEILING THE CHARACTERISTICS OF THE EU CHARISMATIC LEADERS USING PIPRECIA-S METHOD - MIRČETIĆ, Vuk; POPOVIĆ, Gabrijela; VUKOTIĆ, Svetlana (Journal of process management and new technologies, 2024)
One of the popular leadership styles in politics is charismatic leadership, which implies that leaders possess unique qualities that set them apart from others, enabling them to mobilise the masses, gain support, win elections, and inspire them towards a common goal. Although many important studies have been undertaken regarding leaders and evaluating leadership qualities, there is a particular gap regarding examining charismatic leadership competencies using MDCM (Multiple-Criteria Decision-Making) methods. This paper aims to fill the scientific gap and provide a different insight into leadership competencies by evaluating the characteristics of the EU charismatic leaders in the 21st century using the PIPRECIA-S method. Drawing on previous research, this article provides a a more fine-grained perspective of the literature on leadership competencies and using PIPRECIA-S method to rank charismatic leadership competencies of EU leaders, and provide insights into European Union leaders' qualities, focusing on their strengths and areas for development. The findings highlight the importance of specific competencies in effective leadership, such as stability, discernment, education, analytical thinking, and learning from mistakes. This article also displays the effectiveness of MDCM methods in evaluating leadership competencies, providing a robust framework for estimating leadership in political and other contexts. The findings have implications for policymakers, organizations, and individuals seeking to develop leadership competencies in the European Union, candidate countries and beyond.
Keywords: Charismatic leadership; analysis; evaluation framework; MDCM methods; PIPRECIA-S